Influence Quality System Information Management and Utilization of Information Technology to Effectiveness System Information Accountancy - Novien Rialdy; Tiara Putri Annisa Pohan (Strata Business Review, 2023)
The purpose of this study was to determine the effect of the quality of information systems, information systems management, and the use of information technology on the effectiveness of accounting information systems at PT. Ody Lestary Medan, either partially or simultaneously. This study uses a quantitative approach with multiple linear analysis techniques while the data collection technique in this study uses a questionnaire. As for the results of the research partially, the quality of information systems do not affect the effectiveness of accounting information systems. The results of this study concluded that simultaneously there is an influences of Information System quality, Information System Management and Utilization of Accounting Information Technology at PT. Ody Lestary Medan, this can seen by the value of fcount 44,770 > Ftable 2.93. the coefficient of determination (R square) obtained is 0.822, this result means that 82.2% of the Effectiveness of Accounting Information Systems variable can be explained by the variables of Quality of Information Systems, Information Systems Management and Utilization of Accounting Information technology, while the remaining 17.8% is explained by other variable not examined.